Effects of supplemental protein removal on total and acid-resistant E. coli, total coliforms, and performance in finishing steers - M.A. Greenquist; C.M. Gordon; J.J. Sindt; James S. Drouillard; Randall K. Phebus (Kansas Agricultural Experiment Station Research Reports, 2003)
Fifty-four crossbred finishing steers were used to measure the effects of reducing supplemental protein (nitrogen) on feedlot performance and fecal shedding of acid-resistant Escherichia coli and total coliform bacteria. A control diet (15.0% crude protein; high protein) was compared to a low protein diet (8.9% crude protein; low protein) from which supplemental nitrogen sources (urea and soybean meal) were removed for the last 8 days of the feeding period. Fecal E. coli and coliform populations were measured prior to harvest. Removal of supplemental nitrogen from feedlot cattle diets did not substantially reduce populations of acid-resistant fecal E. coli and coliforms. Fecal pH tended to be lower (P=0.11) and the molar percentage of fecal isobutyrate and valerate were lower (P<0.05) for steers receiving low protein diets, but total fecal volatile fatty acid concentrations were not affected by dietary treatment. Dry matter intake tended to be lower (P<0.10) for steers fed low protein diets, whereas daily gains, feed:gain, final weights, dressing percentages, and carcass characteristics were similar for cattle fed low and high protein diets.
Keywords: Cattlemen' s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; Protein removal; E. coli; Total coliforms; Finishing steers